2014
DOI: 10.1111/jam.12662
|View full text |Cite
|
Sign up to set email alerts
|

CYP105-diverse structures, functions and roles in an intriguing family of enzymes inStreptomyces

Abstract: The cytochromes P450 (CYP or P450) are a large superfamily of haem-containing enzymes found in all domains of life. They catalyse a variety of complex reactions, predominantly mixed-function oxidations, often displaying highly regio- and/or stereospecific chemistry. In streptomycetes, they are predominantly associated with secondary metabolite biosynthetic pathways or with xenobiotic catabolism. Homologues of one family, CYP105, have been found in all Streptomyces species thus far sequenced. This review looks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 83 publications
1
32
0
Order By: Relevance
“…p450nor is actinobacterial in origin, yet Actinobacteria are not considered canonical denitrifiers and evidence for their role in denitrification was lacking when p450nor was initially identified (29, 45). Subsequent investigations did not posit a role for p450nor in SM despite the affiliation of p450nor and CYP105 P450s with documented roles in SM (34, 46). To assess genomic evidence linking p450nor to SM, we queried genes encoded within genomic regions approximately 50 kb on either side of p450nor for functions related to SM.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…p450nor is actinobacterial in origin, yet Actinobacteria are not considered canonical denitrifiers and evidence for their role in denitrification was lacking when p450nor was initially identified (29, 45). Subsequent investigations did not posit a role for p450nor in SM despite the affiliation of p450nor and CYP105 P450s with documented roles in SM (34, 46). To assess genomic evidence linking p450nor to SM, we queried genes encoded within genomic regions approximately 50 kb on either side of p450nor for functions related to SM.…”
Section: Resultsmentioning
confidence: 96%
“…The SM hypothesis has traction considering that P450nor is derived from CYP105 P450s (Fig. 2), all of which share a functional role in SM (34, 46, 60). Thus, the adaptation of P450nor to a novel niche in NO reduction and denitrification is unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed the potential role of other types of cytochrome P450 in the biodegradation of hydrocarbons, such as CYP51B, CYP105, CYP123, CYP125 and CYP136. CYP51B was described as a sterol-demethylase (Bellamine et al 1999), CYP105 seems to have diverse functions in catabolism of xenobiotics (Moody and Loveridge 2014. ), while CYP125 was found to catalyze the terminal hydroxylation of steroids (Capyk et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…4 Whilst relatively successful in higher eukaryotes, this approach has limited utility in bacterial systems, where substrate selectivity and catalytic function can vary widely within P450 families -classic examples of P450 families that encompass members displaying highly diverse functions include the CYP105, CYP107 and CYP109 families. 2,3,5,6 Thus, care must be taken in assigning P450 functions in bacteria based purely on sequence conservation data, unless the level of conservation is very high (>55-65%).…”
Section: Introduction To P450smentioning
confidence: 99%